Improvement of grain drying technology through the rapid grain heating and heat recuperation of wet gases - Gaponjuk, Igor (My University, 2017)
The results of theoretical and stand researches of kinetics ofheating moist working gases are in-process expounded.Speed of heating of moist grain by moist gases in 25-35times anymore from methods and traditional modes ofheating. Mathematical models over and rationalmodes ofthe rapid heating of grain are brought before his drying. Results can be drawn on in scientific and practical spheres with grain-growing foods.
Keywords: capillary bodies; motive potential; active surface; moisture; phase environments; сушіння; робочі гази; параметри газів; рушійний потенціал; теплообмін; кафедра технології зберігання і переробки зерна